2009
DOI: 10.1039/b909618c
|View full text |Cite
|
Sign up to set email alerts
|

Water-mediated conformer optimization in benzo-18-crown-6-ether/water system

Abstract: The conformation of benzo-18-crown-6-ether (B18C6) and its encapsulation of water molecules in a supersonic beam are investigated by laser induced fluorescence (LIF), UV-UV hole-burning, IR-UV double resonance (IR-UV DR), and resonance-enhanced multiphoton ionization (REMPI) spectroscopy with the aid of density functional theory (DFT) calculations at the B3LYP/6-31+G* level. At least four B18C6 conformers and nine B18C6-(H2O)n (n = 1-4) clusters are identified in the supersonic beam. IR-UV DR spectra in the CH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 26 publications
5
52
0
Order By: Relevance
“…24,39,40,42,[44][45][46][47][48][49] The highest frequency transition at 3715 cm −1 is readily assignable to a free OH-stretch fundamental. The transitions at 3683 and 3550 cm −1 are similar to those observed in the DPOE-H 2 O spectrum 24 (Figure 1(b) and dotted lines in Figure 6(a)), consistent with a similar primary binding site to DPOE in which one water acts as a double donor bridge between an ether O-atom on one ring and the π cloud on the other (OH · · · π at 3683 cm −1 and OH · · · O at 3550 cm −1 ).…”
Section: Dpoe-(h 2 O)mentioning
confidence: 96%
“…24,39,40,42,[44][45][46][47][48][49] The highest frequency transition at 3715 cm −1 is readily assignable to a free OH-stretch fundamental. The transitions at 3683 and 3550 cm −1 are similar to those observed in the DPOE-H 2 O spectrum 24 (Figure 1(b) and dotted lines in Figure 6(a)), consistent with a similar primary binding site to DPOE in which one water acts as a double donor bridge between an ether O-atom on one ring and the π cloud on the other (OH · · · π at 3683 cm −1 and OH · · · O at 3550 cm −1 ).…”
Section: Dpoe-(h 2 O)mentioning
confidence: 96%
“…As was described above, the flexibility is the key point of crown ethers and they are able to adjust their conformations to fit the size and the shape of the guest species. We show how the structural flexibility affects the dynamics of the encapsulation for two CEs;dibenzo-18-crown-6-ether (DB18C6) and benzo-18-crown-6-ether (B18C6) and their complexes with various neutral molecules ( Kusaka et al, 2007( Kusaka et al, , 2008( Kusaka et al, , 2009 Scheme 4. Dibenzo-18-Crown-6 (DB18C6, left) and Benzo-18-Crown-6(B18C6, right) Figure 14(a) shows the LIF spectrum of DB18C6 cooled in a supersonic jet (Kusaka et al, 2008).…”
Section: Vibrational Spectroscopy Of Gas Phase Functional Molecules Amentioning
confidence: 99%
“…We investigate how the difference in the flexibility affects its conformation as well as its complexation with water. Upper panel of Figure 19 shows LIF spectra of B16C6 in the band origin region observed without and with adding water vapor, respectively (Kusaka et al, 2009). Bands M1-M4 and A-I are due to bare B18C6 and the B18C6-(H 2 O) n complexes, respectively, because the addition of water vapor reduces the intensities of bands M1-M4 and increases bands A-I.…”
Section: B18c6 and Its Complexesmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26][27] The cold gas phase complexes are generated either by the supersonic expansion technique for neutral complexes [18][19][20][21][22][23][24] or by the electrospray ionization (ESI)/cold ion-trap method for ionic complexes. [18][19][20][21][22][23][24][25][26][27] The cold gas phase complexes are generated either by the supersonic expansion technique for neutral complexes [18][19][20][21][22][23][24] or by the electrospray ionization (ESI)/cold ion-trap method for ionic complexes.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26][27] The cold gas phase complexes are generated either by the supersonic expansion technique for neutral complexes [18][19][20][21][22][23][24] or by the electrospray ionization (ESI)/cold ion-trap method for ionic complexes. 20,22,23 In the present work, we report a study on host-guest complexes of CEs with protonated aromatic amines. Based on these studies, we reported that the conformations of CEs in the inclusion complexes are generally different from the most stable conformer of bare forms, because CEs will change their structures so that they can include the different size and structure of guest species in their cavities.…”
Section: Introductionmentioning
confidence: 99%